2018
DOI: 10.1002/eat.22998
|View full text |Cite
|
Sign up to set email alerts
|

Eye‐tracking research in eating disorders: A systematic review

Abstract: Objective: Those with eating disorders (EDs) show attentional biases to disorder-relevant stimuli, such as food and body shape information. However, attentional bias research in EDs largely relies on reaction time based measures, which are limited in their ability to assess different components and the time course of attention. Eye-tracking paradigms have therefore been utilized to provide greater ecological validity, and directly capture the detailed sequence of processes in perception and attention. While nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0
3

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 111 publications
(248 reference statements)
5
57
0
3
Order By: Relevance
“…The current study has a number of strengths. The sample size is one of the largest among eye-tracking studies in individuals with EDs (for a review, see [90]), and it is the first study to measure attention during emotion recognition in both acute and recovered AN. The inclusion of both basic and complex emotions, as well as the use of realistic photo stimuli allowed for a more ecologically valid assessment of emotion recognition abilities.…”
Section: Discussionmentioning
confidence: 99%
“…The current study has a number of strengths. The sample size is one of the largest among eye-tracking studies in individuals with EDs (for a review, see [90]), and it is the first study to measure attention during emotion recognition in both acute and recovered AN. The inclusion of both basic and complex emotions, as well as the use of realistic photo stimuli allowed for a more ecologically valid assessment of emotion recognition abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that women with ED, and individuals with high BD levels, tend to pay more attention to self-defined unattractive body areas, while healthy participants tend to show a more general scanning behavior, covering either the whole body or the most attractive body parts (Freeman et al, 1991;Jansen, Nederkoorn, & Mulkens, 2005;Kerr-Gaffney, Harrison, & Tchanturia, 2019;Rodgers & DuBois, 2016;Roefs et al, 2008;Tuschen-Caffier et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike previous attentional bias reviews including body-and/or food-related stimuli (e.g., Brooks, Prince, et al, 2011;Dobson & Dozois, 2004;Faunce, 2002;Jiang & Vartanian, 2018;Johansson et al, 2005;Kerr-Gaffney, Harrison, & Tchanturia, 2019;Lee & Shafran, 2004), the current review reveals that fMRI was the primary psychophysiological measure used to measure implicit bias in ED, surpassing purely behavioral modified Stroop paradigms that were previously the focus. Historically, fMRI has been more commonly used in anxiety attentional bias studies, finding that fear-related information processing translates to heightened amygdala activation and suggests an automatic hypervigilance toward threat-relevant stimuli (Cisler & Koster, 2010).…”
Section: Comparison With Prior Reviewsmentioning
confidence: 86%